2021
DOI: 10.3389/fmicb.2021.638003
|View full text |Cite
|
Sign up to set email alerts
|

The Emerging Trend of Bio-Engineering Approaches for Microbial Nanomaterial Synthesis and Its Applications

Abstract: Micro-organisms colonized the world before the multi-cellular organisms evolved. With the advent of microscopy, their existence became evident to the mankind and also the vast processes they regulate, that are in direct interest of the human beings. One such process that intrigued the researchers is the ability to grow in presence of toxic metals. The process seemed to be simple with the metal ions being sequestrated into the inclusion bodies or cell surfaces enabling the conversion into nontoxic nanostructure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(14 citation statements)
references
References 252 publications
(264 reference statements)
0
12
0
Order By: Relevance
“…Microalgae purify water through either direct uptake of contaminants or their transformation to harmless products (Dhanker et al, 2021). Algal species are reported to facilitate bacterial degradation of organics by providing oxygen through photosynthesis, which reduces costs and energy expenditure associated with the gassing/stirring process for aeration (Wollmann et al, 2019).…”
Section: The Role Of Bacteria and Microalgae In Wastewater Treatment ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Microalgae purify water through either direct uptake of contaminants or their transformation to harmless products (Dhanker et al, 2021). Algal species are reported to facilitate bacterial degradation of organics by providing oxygen through photosynthesis, which reduces costs and energy expenditure associated with the gassing/stirring process for aeration (Wollmann et al, 2019).…”
Section: The Role Of Bacteria and Microalgae In Wastewater Treatment ...mentioning
confidence: 99%
“…Microalgae cultures offer an elegant solution to tertiary and quaternary treatments due to the ability of microalgae to use inorganic nitrogen and phosphorus for their growth. They are also known for their capacity to remove heavy metals and some toxic organic compounds, thus can also help to prevent secondary pollution (Raouf et al, 2012;Arora et al, 2021;Dhanker et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to that, reports have yielded various evidence that toxicological outcomes to these oocyte cells get increased with Ag molar fractions. Other in vitro models of zebrafish ovary follicular cells around the oocytes, thecal cellular regions, and granulosal cell localities exhibited the apoptotic cell death having the phenotype of irregular cellular morphologies, unorganized cytoplasmic regions that are disunited and fractionated, and condensed nuclear regions post-exposure to silver nanoparticles and silver nitrate ( Ferdous and Nemmar, 2020 ; Dhanker et al, 2021 ). Various in vitro experimentations have also demonstrated that quantum dots conjugated with transferrin molecules can be chiefly uptaken by cumulus cellular structures; however, no quantum dot was able to get entry into the oocyte cells.…”
Section: Nanotoxicology and The Female Reproductive Systemmentioning
confidence: 99%
“…Improved efficiency, productivity, and sustainability have been reported in biologically synthesized AgNPs (Chung et al, 2016). AgNPs are the potential candidates for inhibiting the growth of the bacteria indicating a promising approach for preserving vegetables and fruits (Carmona-Cabello et al, 2018;Dhanker et al, 2021). The objective of the present research article was to synthesize and characterize AgNPs from peels of two vegetables: pea (Pisum sativum) and bottle gourd (Lagenaria siceraria), and to compare their antibacterial activities.…”
Section: Introductionmentioning
confidence: 99%